Modulation of Triton X-100 Aqueous Micelle Interface by Ionic Liquid: A Molecular Level Interaction Studied by Time-resolved Fluorescence Spectroscopy - Pramanik, Rajib; Srivastava, Sagar (Current Physical Chemistry, 2024)
Background: Self-assembly structure is an important area of research for understanding biological systems, owing to its resemblance to the membrane structure of the phospholipid bilayer. In a self-assembly medium, chemical reactions and chemical or physical processes are dramatically different than the bulk phase. Understanding this process in synthesizing self-assembly structures may allow us to explore various biological processes occurring in cell membranes. Objective: The study aimed to understand water dynamics in the TX-100 micellar interface via steady state and a time-resolved fluorescence spectroscopy study. The objective was also to determine the two different ionic liquids (ILs), namely 1-butyl-3-methyl imidazolium tetrafluoroborate ([bmim][BF4]) and 1-decyl-3-methyl imidazolium tetrafluoroborate ([dmim][BF4]), inducing surfactant aggregation changes at the molecular level. Also, the focus was on determining the hydration and its dynamics at the palisade layer of TX-100 micelle in the presence of two different ionic liquids. Methods: Steady state and time-resolved fluorescence spectroscopy have been used to study TX-100 micellar systems. Employing time-resolved spectroscopy, two chemical dynamic processes, solvation dynamics and rotational relaxation dynamics, have been studied to investigate structural changes in TX100 by adding ILs. Solvation dynamics was studied by measuring the time-dependent Stokes shift of the fluorescent probe. From the Stokes shift, time-resolved emission spectra were constructed to quantify the solvation dynamics. Also, using the polarization properties of light, time-resolved anisotropy was constructed to explore the rotation relaxation of the probe molecule. Results: The absorption and emission spectra of C-153 in TX-100 were red-shifted in the presence of both the ILs. Also, the C-153 experienced faster solvation dynamics and rotational relaxation with the addition of both ILs. In our previous study, we observed a significantly increased rate of solvation dynamics with the addition of [bmim][BF4] (J. Phys. Chem. B, 115, 6957-6963) [38]. However, with the addition of the same amount of [dmim][BF4], the IL rate of solvation enhancement was more pronounced than with [bmim][BF4]. The faster solvation and rotational relaxation have been found to be associated with the penetration of more free water at the TX100 micellar stern layer, leading to increased fluidity of the micellar interface. Conclusion: Upon incorporating ILs in TX100 micelle, substantially faster solvation dynamics of water as well as rotational relaxation dynamics of C-153 have been observed. By decreasing surfactant aggregations, [bmim][BF4] ILs facilitated more water molecules approaching the TX-100 micellar phase. On the other hand, [dmim][BF4] ILs comprising mixed micelles induced even more free water molecules at the palisade layer, yielding faster solvation dynamics in comparison to pure TX-100 micelle or TX100 micelle + [bmim][BF4] ILs systems. Time-resolved anisotropy study has also supported the finding and strengthened the solvation dynamics observation.
Keywords: fluidity